iTRAQ protein profile analysis of neuroblastoma (NA) cells infected with the rabies viruses rHep-Flury and Hep-dG - Yang, Youtian; Liu, Wenjun; Luo, Yongwen; Yan, Guangrong; Zhao, Jing; Yang, Xianfeng; Mei, Mingzhu; Wu, Xiaowei; Guo, Xiaofeng (Frontiers in Microbiology, 2015)
The rabies virus (RABV) glycoprotein (G) is the principal contributor to the pathogenicity and protective immunity of RABV. In a previous work, we reported that recombinant rabies virus Hep-dG, which was generated by reverse genetics to carry two copies of the G-gene, showed lower virulence than the parental virus rHep-Flury in suckling mice with a better immune protection effect. To better understand the mechanisms underlying rabies virus attenuation and the role of glycoprotein G, isobaric tags for relative and absolute quantitation (iTRAQ) was performed to identify and quantify distinct proteins. 10 and 111 differentially expressed proteins were obtained in rHep-Flury and Hep-dG infection groups, respectively. Selected data were validated by western blot and qRT-PCR. Bioinformatics analysis of the distinct protein suggested that glycoprotein over-expression in the attenuated RABV strain can induce activation of the interferon signaling. Furthermore, it may promote the antiviral response, MHC-I mediated antigen-specific T cell immune response, apoptosis and autophagy in an IFN-dependent manner. These findings might not only improve the understanding of the dynamics of RABV and host interaction, but also help understand the mechanisms underlying innate and adaptive immunity during RABV infection.